Globalization through global citizenship and right to migrate - Sunil K. Raina; Raman Kumar (Journal of Family Medicine and Primary Care)
All human beings of the world should be equal in status and stature. However, in reality human beings are divided by citizen status of nation states that are members of the United Nations. The human development index differs from one nation to another. Therefore quality of life, health, and life expectancy varies across countries and continents. Much depends on the governments representing human groups living in defined territorial boundaries. Governments defend sovereign territories and compete with other governments for business monopolies, territories and natural resources. From empires to colonisation, the world is passing through the phase of globalisation. There is an uneven divide of natural planetary resources and geographical territories. Also there is a continuous flow of financial resources from the poor nation states and in favour of the rich ones. Globalisation can no longer remain a refined chaotic balance of exploitation of one human territory by another. Travel and migration from one territory to another are highly regulated. The true idea of Globalization will only be realised when it is not linked to race, the level of skills, political affiliation or economic dividends and is able to add to the upward movement of the social structure of the poor. In a globalised world there should be equitable and fast paced distribution of benefits of modern development. Otherwise the global citizens of the world should look for alternatives.